Subacute SARS-CoV-2 replication can be controlled in the absence of CD8+ T cells in cynomolgus macaques - Nomura, Takushi; Yamamoto, Hiroyuki; Nishizawa, Masako; Hau, Trang Thi Thu; Harada, Shigeyoshi; Ishii, Hiroshi; Seki, Sayuri; Nakamura-Hoshi, Midori; Okazaki, Midori; Daigen, Sachie; Kawana-Tachikawa, Ai; Nagata, Noriyo; et al. (PLoS pathogens, 2021)
SARS-CoV-2 infection presents clinical manifestations ranging from asymptomatic to fatal respiratory failure. Despite the induction of functional SARS-CoV-2-specific CD8 + T-cell responses in convalescent individuals, the role of virus-specific CD8 + T-cell responses in the control of SARS-CoV-2 replication remains unknown. In the present study, we show that subacute SARS-CoV-2 replication can be controlled in the absence of CD8 + T cells in cynomolgus macaques. Eight macaques were intranasally inoculated with 10 5 or 10 6 TCID 50 of SARS-CoV-2, and three of the eight macaques were treated with a monoclonal anti-CD8 antibody on days 5 and 7 post-infection. In these three macaques, CD8 + T cells were undetectable on day 7 and thereafter, while virus-specific CD8 + T-cell responses were induced in the remaining five untreated animals. Viral RNA was detected in nasopharyngeal swabs for 10–17 days post-infection in all macaques, and the kinetics of viral RNA levels in pharyngeal swabs and plasma neutralizing antibody titers were comparable between the anti-CD8 antibody treated and untreated animals. SARS-CoV-2 RNA was detected in the pharyngeal mucosa and/or retropharyngeal lymph node obtained at necropsy on day 21 in two of the untreated group but undetectable in all macaques treated with anti-CD8 antibody. CD8 + T-cell responses may contribute to viral control in SARS-CoV-2 infection, but our results indicate possible containment of subacute viral replication in the absence of CD8 + T cells, implying that CD8 + T-cell dysfunction may not solely lead to viral control failure.